Performance of Hourly Rainfall Simulations using WRF Meteorological Model for Calculation of Streamflow to Ta Trach Reservoir During 2020 Flood Season - Tien Thanh, Nguyen; Thai Son, Nguyen; Duc Mien, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 1DO - 10.25073/2588-1094/vnuees.4898, 2023)
More and more extreme weather events are frequently observed in Thua Thien Hue province in recent years, especially in 2020. Only 7 days from October 6-12, 2020, total rainfall measured at Thuong Nhat station is approximately 1900 mm, accounting for more than 50% of the total annual rainfall. So, it is necessary to ensure the effective operation for Ta Trach reservoir, a large reservoir with a basin area of ​​717 km 2 in Thua Thien Hue. This study is initially to clarify the performance of hourly rainfall simulations and streamflow to Ta Trach reservoir using WRF and HEC-HMS hydro-meteorological models during the 2020 flood season, respectively. The results showed that on the scale of daily, the correlation between simulated and measured rainfall is quite good, most of the stations could be reached about 0,8. On the scale of hourly, these figures are about 0,5 and the trend of cumulative hourly rainfall simulated is consistent with measured values. Especially, the trend of simulated streamflow using directly hourly rainfall from WRF model to Ta Trach reservoir is consistent with the measurement streamflow although the errors are still seen to extent with the NASH index of about 0,65.